Games Technology as Innovative Tool for Forming a Library and Information Environment of Knowledge Management - Hranchak, T.Yu. (Science and Innovation, 2024)
Introduction. The need to increase the efficiency of using available information and knowledge, creating conditions for the production of new knowledge and sharing this new knowledge makes studying the cognitive potential of game technologies very relevant. Problem Statement. The fulfillment of game potential as innovative technology for the formation of a library and information knowledge management environment. Purpose. To substantiate the necessity to introduce game technologies into the library practice in order to ensure an effective involvement of libraries in knowledge management; to develop theoretical and methodological approaches to organizing a game library and information environment. Materials and Methods. The reference database of the research is library websites, thematic resources (International Games Week American Library Association portal and Zooniverse game platform), specialized literature: publications dealing with involvement of libraries in knowledge management processes, which highlight the experience of applying game technologies to education, research, and libraries. The systemic, functional, observation, hypothesis methods in combination with the social communication method have been used. Results. The expediency of introducing game technologies as innovative knowledge management tool into the library practice within the framework of implementing the social role of libraries in preserving, cumulating, organizing, and spreading knowledge has been substantiated; the cognitive potential of game technologies has been shown; theoretical and methodological principles of introducing game technologies into the library practice have been offered; examples of effective use of gaming technology by domestic and foreign libraries have been highlighted. Conclusions. A favorable effect of using the game cognitive potential in educational practice and scholarly research has resulted in the need to develop strategies for introducing game technologies as innovative knowledge management tool into the activities of library institutions.